The Effect Of Training And Compensation On Health Workers Performance At dr. Soepraoen Hospital Malang - Achmad Jaelani Rusdi; Fita Rusdian Ikawati; Anis Ansyori; Rengganis Ularan; Dewi Anggraeni (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
This study aims to examine the effect of independent variables (training and compensation) on health performance in Kindergarten Hospitals. II dr. Soepraoen Malang. Data obtained from questionnaires and interviews. The sample in this study were 90 respondents who were taken using the saturated sample method. The data collectiontechnique used was the questionnaire technique which was distributed directly to the respondents, in this case the healthperformance of the Kindergarten II Dr. Soepraoen Hospital,Malang. The data analysis technique used multiple linear regression analysis. Thisresearch uses reliability test techniques, validation and classical assumptions. The resultsof this study indicate that the independent variables (trainingand compensation) have a positive and significant effect on employee performance.